Hospital pharmacists' perspectives on the role of key performance indicators in Australian pharmacy practice. (24th December 2016) - Lloyd, Georgia F.; Singh, Shamsher; Barclay, Peter; Goh, Sue; Bajorek, Beata
Abstract: Background: To date, there is no national or international consensus on which key performance indicators (KPIs) should be used to measure hospital pharmacy performance. Aim: To explore hospital pharmacists' perspectives on the role of KPIs and to use their perspectives to suggest a set of KPIs for use in Australian hospital pharmacy practice. Methods: The study comprised of two parts. Part A involved semi‐structured interviews with hospital pharmacists from major Sydney metropolitan hospitals; interviews were conducted until theme saturation was attained. Part B involved an online survey comprising Likert‐scale responses and open‐ended questions; the survey was distributed nationally to pharmacists via the Society of Hospital Pharmacists of Australia (SHPA) eNewsletter and Facebook page. Results: Part A: 19 hospital pharmacists were interviewed. Part B: 49 online surveys were received (after excluding incomplete submissions). Overall, the emergent themes identified that hospital pharmacists agreed that KPIs are a valuable tool for individual and departmental performance measurement; the use of KPIs was challenged by data collection difficulties, a lack of engagement from staff, and a lack of clarification regarding the intended use of KPIs and their relevance. The study identified a consolidated set of seven KPIs, proposed as standard measures for hospital pharmacy practice. Conclusion: There is a perceived need to develop national standardised KPIs to demonstrate the value of pharmacy services at the individual and departmental levels. However, there are challenges that will need to be addressed before the implementation of a set of consolidated KPIs that encompasses the full scope of pharmacy activities.